2021
DOI: 10.1093/bjs/znab299
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of outcomes of emergency general and gastrointestinal surgery during the COVID-19 pandemic

Abstract: Background Few surgical studies have provided adjusted comparative postoperative outcome data among contemporary patients with and without COVID-19 infection and patients treated before the pandemic. The aim of this study was to determine the impact of performing emergency surgery in patients with concomitant COVID-19 infection. Methods Patients who underwent emergency general and gastrointestinal surgery from March to June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
1
19
0
1
Order By: Relevance
“…When resources are constrained, operating upon patients more likely to have a good outcome reduces the strain on precious critical care resources and risk stratification should be considered. It is also possible that the higher peak mortality rate was related to a failure to rescue patients following complications due to resource constraints caused by the pandemic, also seen in a Spanish study of emergency general and gastrointestinal surgery patients ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…When resources are constrained, operating upon patients more likely to have a good outcome reduces the strain on precious critical care resources and risk stratification should be considered. It is also possible that the higher peak mortality rate was related to a failure to rescue patients following complications due to resource constraints caused by the pandemic, also seen in a Spanish study of emergency general and gastrointestinal surgery patients ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 15 (44%) of the 34 patients with confirmed infection required ICU management, with a postoperative mortality rate of 20.5% [ 37 ]. Osorio J, et al also reported that COVID-19 positive patients who underwent emergency general and gastrointestinal surgery during the pandemic had more complications and a higher likelihood of failure rescue than COVID-19 negative patients [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, to assess the impact of COVID-19 infection on postoperative mortality, COVID-19-positive patients were compared with COVID-19-negative patients operated on during the pandemic using propensity-score matching, matching patients with similar age, baseline pathologies and general condition at the time of surgery. Although the crude postoperative mortality of the two groups was very different (12.6% vs. 4.6%), this difference did not reach statistical significance after propensity-score matching (odds ratio 1.58, 95% CI .88-2.74) 3 . In other words, the high mortality observed in COVID-19 infected patients undergoing emergency surgery was due more to their age, underlying pathology and preoperative clinical status than to a hypothetical synergistic effect of the virus.…”
mentioning
confidence: 81%
“…At the same time, to assess the effect of confinement, the surgical pathology status of the COVID-19-negative patients operated on during the pandemic was compared with those operated on the previous year. It was found that, during the pandemic, the patients did not present more advanced peritonitis or greater surgical complexity, and the inflammatory parameters of their analyses did not show higher values 3 . Thus, the higher mortality observed during the pandemic could not be attributed to patients consulting later due to confinement.…”
mentioning
confidence: 92%
See 1 more Smart Citation